2021
DOI: 10.9767/bcrec.16.3.10757.491-506
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Ponceau 4R in Aqueous Solution using Iron-impregnated Al-pillared Bentonite: Optimization of the Process

Abstract: The application of the Fenton-like process for the oxidation of an aqueous solution of Ponceau 4R dye, using an aluminum pillared clay impregnated with iron (Fe(wt%)/Al-PILC) as catalyst, was investigated. The Response Surface Methodology (RSM), based on a Central Composite Design (CCD) was used to evaluate and optimize the oxidation process of a Ponceau 4R solution. Three independent variables were studied in the experimental design: the amount of H2O2 expressed in multiples of times of stoichiometry dose, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In the case of dyes, these compounds are of particular interest because they inhibit photosynthetic processes in water bodies, are toxic to some aquatic species, and may even affect human health. This is why several authors have reported the removal of azo dyes using PILCs in CWPO processes [ 50 , 67 , 68 ]. Between 1980 and 2019, the most commonly used dyes as model molecules in scientific publications for the treatment of colored wastewater, using AOP/PILC systems, are methylene blue (23%), methyl orange (12%), orange II (12%), rhodamine B (10%), malachite green (7), among others (36%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of dyes, these compounds are of particular interest because they inhibit photosynthetic processes in water bodies, are toxic to some aquatic species, and may even affect human health. This is why several authors have reported the removal of azo dyes using PILCs in CWPO processes [ 50 , 67 , 68 ]. Between 1980 and 2019, the most commonly used dyes as model molecules in scientific publications for the treatment of colored wastewater, using AOP/PILC systems, are methylene blue (23%), methyl orange (12%), orange II (12%), rhodamine B (10%), malachite green (7), among others (36%).…”
Section: Resultsmentioning
confidence: 99%
“…is is why several authors have reported the removal of azo dyes using PILCs in CWPO processes [50,67,68]. Between 1980 and 2019, the most commonly used dyes as model molecules in scientific publications for the treatment of colored wastewater, using AOP/PILC systems, are methylene blue (23%), methyl orange (12%), orange II (12%), rhodamine B (10%), malachite green (7), among others (36%).…”
Section: Resultsmentioning
confidence: 99%
“…Metal polyhydroxy cation-pillared bentonites, such as Al, Ti, and Fe, show higher thermal stability than organic cation-pillared bentonites. 26) Several metals have been investigated for their potential as pillar agents, such as Al-PILC, 28,31,49) Zr-PILC, 14,26,34,46,[51][52][53][54] Ti-PILC, 45,49,56) Mo-PILC, 57) and Cr-PILC. 30,58) In current developments, researchers are beginning to explore the use of combined metal oxide pillars to enhance surface properties and acidity in bentonite, including Al/Zr-PILC, 19,45) Al/Fe-PILC, 47,59) Al/ Co-PILC, 22) Al/Cr-PILC, 30) Al/Fe/Ni-PILC, 60) Fe/Cr-PILC, 58) Ni/Zr-PILC, 61) Mg/Al-PILC.…”
Section: The Bentonite Modification Using the Pillarization Methodsmentioning
confidence: 99%
“…They found that the low surface area and low acidity of bentonite limited the active sites available for catalysis, resulting in lower conversion rates than Al-pillared bentonite. Research by AlSawalha et al 46) focused on the acidic properties of various Jordanian clays, including bentonite, kaolinite, and diatomite, for conversion 2-methyl-3-butyn-2-ol (MBOH). The maximum NH 3 desorption rate from the zeolite surface is the highest and decreases from bentonite to kaolinite and diatomite.…”
Section: Structure and Physico-chemical Properties Of Bentonitementioning
confidence: 99%